Analysis of The Feasibility of Revitalization of The Type a Amplacing Terminal and The Performance of The Sisingamangaraja Road Section, Medan - Dodi Frenky; Sinar Indra Kesuma; Satia Negara Lubis (Yayasan Multidimensi Kreatif, 2023)
The main objective of this research is to analyze and find out if the investment plan is profitable in the future so that it is feasible or not to be implemented. Apart from that, this research also aims to analyze the Operational Performance of the Sisingamngaraja Road Section which includes: Side Obstacles, Free Flow Speed, Travel Speed and Time, and Service Level. The data used in this research are primary data and secondary data. Primary data was obtained through interviews and observations. Meanwhile, secondary data was obtained from related agencies or services such as the Medan City Transportation Department. The analytical method used in this research uses two analytical tools, namely investment feasibility analysis and road segment performance analysis. The research results obtained from the Net Present Value for the next 10 years are IDR. 60,400,000. shows that it is feasible to revitalize the Amplas Type A Terminal. This can be proven from the investment acceptance criteria and the NPV method, namely if the calculation results show that the value is positive then the investment is worth implementing. From the calculation results, the IRR of 30.5% shows that the interest rate will equal the present value of the investment. With present value, the value of net cash receipts in the future. As a criterion for acceptance of this method, if the calculated interest rate is greater than the desired interest rate, the investment is accepted. In this case the interest rate is 20%, so the IRR of 30.5% is said to be feasible for the revitalization of the Amplas Type A Terminal. The Profitability Index (PI) is 1.10 (accepted) because PI > 1. From the results of the Payback Period calculation, the Payback period for the revitalization of the Amplas Type A Terminal is 22.2 years. This means it is shorter than the economic investment period, namely 35 years, so the Payback Period criteria for the revitalization of the Amplas Type A Terminal can be accepted because it is lower than the useful life period. The performance of the section on Jalan Sisingamngaraja by determining the size of the road capacity and traffic volume is known to still have problems with congestion during peak activity hours.